Expanding access to safe abortion in DRC: charting the path from decriminalisation to accessible care - Annie L. Glover; Jean-Claude Mulunda; Pierre Akilimali; Dynah Kayembe; Jane T. Bertrand (Sexual and Reproductive Health Matters)
Access to safe and comprehensive abortion care has the potential to save thousands of lives and prevent significant injury in a vast and populous country such as the Democratic Republic of the Congo (DRC). While the signing of the Maputo Protocol in 2003 strengthened the case for accessible abortion care across the African continent, the DRC has grappled with de jure ambiguity resulting in de facto confusion about women’s ability to access safe, legal abortion care for the past two decades. Conflicting laws and the legacy of the colonial penal code created ambiguity and uncertainty that has just recently been resolved through medical and legal advocacy oriented towards facilitating an enabling policy environment that supports reproductive healthcare. A study of the complex – and frequently contradictory – pathway from criminalised abortion to legalisation that DRC has taken from ratification of the protocol in 2008 to passage of the 2018 Public Health Law and subsequent Ministry of Health guidelines for abortion care, is an instructive case study for the international sexual health and reproductive rights community. Through this analysis, health and legal advocates can better understand the interdependence of law and public health and how a comprehensive approach to advocacy that includes legal, systems, and clinical accessibility can transform a country’s system of care and the protection of women’s rights. In DRC, new legislation and service delivery guidelines demonstrate a path forward towards concrete improvements for safe abortion care.